Poaching international students? A study of an Australian university with metropolitan campuses. (2nd January 2022) - Shah, Mahsood; Mahadevan, Kumaraguru; Cheng, Ming
ABSTRACT: International higher education is the third largest export industry in Australia. Student attrition is an area of concern in higher education institutions. Most research undertaken so far has focused on domestic student attrition in Australia and globally. This study focuses on an Australian university to examine the causes of international students' attrition after their first year of study. It reveals that since 2018, growing numbers of international students have withdrawn from the subject university at the metropolitan campus to enrol in private colleges attracted by lower tuition fees for similar degree qualifications. The paper raises questions about the role of education agents in such student mobility and risks related to academic standards and quality in private colleges. The paper also raises questions about risks to quality and competitiveness in universities that have not sufficiently considered the academic and personal needs of international students.